Stress Analysis And Modal Transient Response Of Car Chassis - M. S. M., Sani; M. M., Noor; T. T., Mon (2009)

(untitled)
This paper discusses the computational modal transient response and stress analysis of car chassis. The prediction of the dynamic properties of the chassis is great significant to determine the natural frequencies of the structure. In order to avoid resonance, value operating frequency must lower than natural frequency of the chassis. Stress analysis was carried out by using Algor FEMPRO Software to determine the stress distribution on the chassis structure when load been applied. Result shows that bending mode observe at first mode frequency, torsion mode at second mode frequency , mixed bending and torsion at third mode frequency and bending mode at fourth mode frequency. Range natural frequency from 50-99 Hz was examined on this analysis. Maximum stress, 45 MPa was determined at each corner at pillar joint and this value is under the allowable stress for steel which is 300 MPa. The stress and modal analysis techniques are significant essential for automotive chassis structure design.